Early psychological impact of Paris terrorist attacks on healthcare emergency staff: A cross‐sectional study. Issue 3 (8th February 2018) - De Stefano, Carla; Orri, Massimiliano; Agostinucci, Jean Marc; Zouaghi, Haroun; Lapostolle, Frederic; Baubet, Thierry; Adnet, Frederic
Abstract : Background: The terrorist attacks in Paris and Saint Denis on November 13, 2015 were an unprecedented traumatic event in France. It was an especially distressing ordeal for the healthcare personnel involved in the care of the victims. The aim of this study was to estimate the effect of direct participation in the rescue on posttraumatic stress disorder (PTSD) symptoms among these workers. Methods: Less than a month later, 613 healthcare providers (professionals and paraprofessionals) from three hospitals in the Paris suburbs were asked to complete an anonymous questionnaire. A multivariable Poisson model estimated the effect of participating onsite in the rescue (exposure variable) on the number of PTSD symptoms measured by the Trauma Screening Questionnaire (TSQ; outcome variable), adjusted for covariates. Results: Two hundred thirty‐three providers completed the assessment (38% response rate), 130 participated directly in the rescue (56%). Participation was associated with a higher number of symptoms of PTSD (RR = 1.34, P = .002) than for nonparticipants. Female gender (RR = 1.39, P < .001) and basic (vs. advanced or intermediate) life‐saving training (RR = 1.42, P = .004) were also associated with more PTSD symptoms. Participants in the rescue were at 2.76 times more risk of a probable PTSD diagnosis (OR = 2.76, P = .037), defined as reporting at least six PTSD symptoms. Sensitivity analyses using propensity score matching supported the robustness of our findings. Conclusions: Healthcare providers directly involved in the rescue of the victims of the Paris and Saint Denis attacks reported a significantly higher psychological impact, defined by PTSD symptoms, than those not directly involved.